Sustained Plateau Activity Precedes and Can Generate Ictal-Like Discharges in Low-Cl(−) Medium in Slices from Rat Piriform Cortex - Demir, Rezan (J Neurosci, 1999)
Interictal and ictal discharges represent two different forms of abnormal brain activity associated with epilepsy. Ictal discharges closely parallel seizure activity, but depending on the form of epilepsy, interictal discharges may or may not be correlated with the frequency, severity, and location of seizures. Recent voltage-imaging studies in slices of piriform cortex indicated that interictal-like discharges are generated in a two-stage process. The first stage consists of a sustained, low-amplitude depolarization (plateau activity) lasting the entire latent period prior to discharge onset. Plateau activity takes place at a site distinct from the site of discharge onset and serves to sustain and amplify activity initiated by an electrical stimulus. In the second stage a rapidly accelerating depolarization begins at the onset site and then spreads over a wide region. Here, we asked whether ictal-like discharges can be generated in a similar two-stage process. As with interictal-like activity, the first sign of an impending ictal-like discharge is a sustained depolarization with a plateau-like time course. The rapidly accelerating depolarization that signals the start of the actual discharge develops later at a separate onset site. As found previously with interictal-like discharges, local application of kynurenic acid to the plateau site blocked ictal-like discharges throughout the entire slice. However, in marked contrast to interictal-like activity, blockade of synaptic transmission at the onset site failed to block the ictal-like discharge. This indicates that interictal- and ictal-like discharges share a common pathway in the earliest stage of their generation and that their mechanisms subsequently diverge.